2015
DOI: 10.1002/ejic.201500948
|View full text |Cite
|
Sign up to set email alerts
|

Hydride Abstraction and Deprotonation – an Efficient Route to Low Coordinate Phosphorus and Arsenic Species

Abstract: Treatment of Acenap(PiPr 2 )(EH 2 ) (Acenap = acenaphthene-5,6-diyl; 1a, E = As; 1b, E = P) with Ph 3 C·BF 4 resulted in hydride abstraction to give [Acenap(PiPr 2 )(EH)][BF 4 ] (2a, E = As; 2b, E = P). These represent the first structurally characterised phosphino/arsino-phosphonium salts with secondary arsine/phosphine groups, as well as the first example of a Lewis base stabilised primary arsenium cation. Compounds 2a and 2b were deprotonated with NaH to afford low co-ordinate species Acenap(PiPr 2 )(E) (3a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“… Selected structurally characterised peri -substituted pnictine-pnictine donor–acceptor complexes, indicating their structural diversity [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. …”
Section: Figures Scheme and Tablementioning
confidence: 99%
“… Selected structurally characterised peri -substituted pnictine-pnictine donor–acceptor complexes, indicating their structural diversity [ 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. …”
Section: Figures Scheme and Tablementioning
confidence: 99%
“…[ 18 ] The chemistry of the acenaphthene di‐substituted in peri ‐position with large atoms and groups has been disclosed by Petr Kilian and co‐workers who prepared and studied several acenaphthene derivatives symmetrically and unsymmetrically substituted with phosphorus, tin, thallium, antimony, bismuth, etc. [ 19–23 ] Furthermore, a systematic study on acenaphthene derivatives peri ‐substituted with a diphenylphosphino group and elements of groups 13 and 15 has been reported by Chęcińska, Beckmann, and co‐workers. [ 24 ] Recently, the group of Kilian has reported a detailed study of the coordination chemistry of the unsymmetrical ligand i Pr 2 P‐Ace‐PPh 2 (Figure 1) with several transition metal ions showing that the ligand forms square‐planar complexes with group 10 d 8 metal ions {[( i Pr 2 P‐Ace‐PPh 2 )MX 2 ], M = Ni, Pd, Pt; X = Cl, Br}.…”
Section: Introductionmentioning
confidence: 99%
“…However, the only examples of crystallographically characterized protonated phospha-or arsanylidenephosphoranes were published by Kilian et al in 2016. [22] . [75] The pathway described herein provides another practical, simple way to access H-substituted phosphino-phosphonium-cations via direct protonation and stabilization through a weakly coordinating anion.…”
Section: I: Mes Termentioning
confidence: 99%
“…[15] Since the first reports by Burg and Mahler in the 1960s, [16,17] a number of stable, mostly aryl-substituted or acenaphtene-based, metal-free phosphanylidene-σ 4 -phosphoranes have been reported. [8,[18][19][20][21][22][23] Aryl-substituted variants have been first described by Protasiewicz and co-workers and it was shown that these systems cleanly react with aldehydes to generate phosphaalkenes akin to the formation of alkenes in the classical Wittig reaction. [8] In addition, phosphanylidenephosphoranes show phosphinidene-like reactivity, which was demonstrated by a series of ligand-deconstruction reactions and diphosphene (RP)2 formation upon photochemically-induced PMe3 release in Ar−P(PMe3) (Ar = Mes*, Mes Ter, Tip Ter).…”
Section: Introductionmentioning
confidence: 99%